Clinical and dosimetric predictors of late rectal bleeding of prostate cancer after TomoTherapy intensity modulated radiation therapy. Issue 3 (1st February 2017) - Katahira‐Suzuki, Ryoko; Omura, Motoko; Takano, Shoko; Matsui, Kengo; Hongo, Hideyuki; Yamakabe, Wataru; Nagata, Hironori; Hashimoto, Harumitsu; Miura, Ichiro; Inoue, Tomio
Abstract: Introduction: Rectal bleeding after radiotherapy impacts the quality of life of long‐term surviving prostate cancer patients. We sought to identify factors associated with late rectal bleeding following intensity modulated radiation therapy (IMRT) using TomoTherapy for prostate cancer. Methods: We retrospectively analysed 82 patients with localised prostate cancer treated with TomoTherapy. Most patients (95.1%) received neoadjuvant and concurrent hormone therapy. Forty‐two patients (51.2%) graded as high risk using D'Amico's classification underwent radiotherapy involving the pelvic nodal area. Late bleeding complications were quantified using the Common Terminology Criteria for Adverse Events v4.0. Multiple clinical and dosimetric factors were considered with reference to rectal bleeding. Results: The median follow‐up period was 538 (range, 128–904) days. Grades 1, 2 and 3 rectal bleeding were observed in 14 (17.1%), four (4.9%) and one (1.2%) patient respectively. In multivariate analysis, the following factors were significantly associated with Grade ≥1 late rectal bleeding: volume, mean dose ( P = 0.012) and rectal V30 ( P = 0.025), V40 ( P = 0.011), V50 ( P = 0.017) and V60 ( P = 0.036). When exclusively considering Grade 2–3 rectal bleeding, significant associations were observed with the use of anticoagulants or antiaggregates ( P = 0.007), rectal V30 ( P = 0.021) and V40 ( P = 0.041) in univariate analysis. Conclusions: Our results suggested that the intermediate rectal dose‐volume (V30–V60) was a significant predictor for mild to severe late rectal bleeding (Grade ≥1). Rectal dose‐volumes >V70, which represented the volume of the highest doses, were not predictive in this study. Abstract : We found the volume of intermediate doses to the rectum was a significant predictor of mild to severe late rectal bleeding in prostate cancer TomoTherapy.